Woolly stops the train: usborne farmyard tales - Cartwright, Stephen; Amery, Heather (Usborne London, 2002)
This is one of a series of pocket-sized editions of Farmyard Tales, all about Poppy, Sam and all the animals who live on Apple Tree Farm. There is also a little yellow duck to spot on every page.